Boosting Communicative English Proficiency: A Study on Students at State Islamic University of Mataram - Wulandari, Putri; Mugni Assapari, Muhammad (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2024)
In the field of language education, assessing students' English competency provides critical insights for effective teaching tactics and curriculum design. The goal of this paper is to assess students' English proficiency and communication skills in a specific academic setting. This qualitative study employs a descriptive approach to explore students' communicative capacities at the English Language Study Programmer, State Islamic University of Mataram, during the academic year 2023-2024. Data are gathered by observation, questionnaires, and interviews. According to the findings of this article, students in the third semester experience substantial obstacles in their English communication skills, particularly in vocabulary, grammar, pronunciation, and lack of English usage. Motivation to improve these skills is critical for student development. highlighting the importance of effective communication and the obstacles faced by students, highlighting the importance of good communication, student challenges, improvement options, and broader implications for academic and career success. English learners must have a high level of enthusiasm and confidence to acquire fluent English. To increase student involvement, English lecturers should emphasize the importance of language in today's world and use efficient teaching approaches. Future scholars should seek out fresh insights into English-speaking skills to successfully assist students and educators.